The slowest timescales of neural synchronization reveal the strongest influence of auditory distraction - Sorensen, David O.; Sugai, Jenna A.; Parthasarathy, Aravindakshan; Hancock, Kenneth E.; Polley, Daniel B. (Frontiers in Human Neuroscience, 2025)
IntroductionAmong all the sounds occurring at any given time, people are often interested in listening to just one. Some competing sounds are merely background noise, whereas others distract attention from target sounds and are less easily suppressed. During active listening, the central auditory pathway unmixes target and distractor sounds based on temporal differences across three orders of magnitude – from millisecond differences in acoustic temporal fine structure to slower perceptual grouping factors that stretch out to multiple seconds. We developed an approach to directly measure central auditory encoding of multiplexed target and distractor sound features in human listeners to determine which timescales are most impacted by the presence of distracting sounds.MethodsTarget sounds contained nested features along four timescales, including temporal fine structure (~500 Hz), temporal envelope (~25–80 Hz), envelope changes (~7 Hz), and slower changes reflecting whether target stimuli were randomly arranged or formed a repeating pattern (~0.5 Hz). Targets were presented with competing sounds that provided variable distraction levels: either a highly distracting melody or a less distracting noise. Neural synchronization to each timescale was simultaneously measured for target and distractor sounds from electroencephalogram (EEG) recordings during a listening task.ResultsSustained shifts from random to regular sequence arrangements were reliably perceived, yet did not evoke a pattern recognition potential, nor neural synchronization changes at any timescale. Synchronization to relatively slow changes in envelope transitions of the target sound deteriorated with the addition of more distracting sounds while synchronization to more rapid fluctuations in the fine structure or envelope were unaffected by varying distraction level. Categorizing trials by task performance revealed a conjunction of enhanced entrainment to slower temporal features in the distractor sound and reduced synchronization to the target sound on error trials.DiscussionBy designing a stimulus paradigm that leveraged the temporal processing capabilities of the auditory nervous system, we were able to simultaneously quantify multiple target and distractor sound features reproduced in the EEG. This paradigm identified synchronization processes which may prove valuable for research on clinical populations who report difficulty suppressing awareness of distracting sounds.